Generalized risk premia - Schneider, Paul (Journal of Financial Economics, 2015)
This paper develops an optimal trading strategy explicitly linked to an agent׳s preferences and assessment of the distribution of asset returns. The price of this strategy is a portfolio of implied moments, and its expected excess returns naturally accommodate compensation for higher-order moment risk. Variance risk and the equity premium approximate it to first order and it nests cross-sectional asset pricing models such as the linear Capital Asset Pricing Model (CAPM). An empirical study in the US index market compares the investment behavior of an agent with recursive long-run risk preferences to one who merely uses an identically independently distributed time series model and takes market prices as given. The two agents exhibit very similar behavior during crises and can be distinguished mostly during calm periods.